New Techniques in Marine Aquaculture - Ma, Zhenhua; Qin, Jianguang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint delves into the latest advancements in aquaculture techniques emerging from China. It provides a comprehensive update on the research and technological developments in various aspects of aquaculture, including biotechnology, ecotechnology, feeding technology, and environmental technology. The reprint covers a wide range of topics, such as the use of biotechnology to identify and characterize genes that enhance resistance to bacterial infection and environmental stress. It also explores feeding technology that improves immunity and stress resistance in aquatic organisms. Additionally, the reprint discusses the detection of the impact of thermal stress on marine fish immunity, the manipulation of light color to enhance algal growth, and the utilization of integrated multi-trophic systems to boost production. With a focus on marine fish, shrimp, sea cucumbers, sea urchins, and algae, this reprint showcases groundbreaking research that paves the way for future advancements in aquaculture. These innovative technologies are expected to have far-reaching implications for other species in the field of aquaculture.